2012
DOI: 10.1111/1556-4029.12019
|View full text |Cite
|
Sign up to set email alerts
|

Rib Butterfly Fractures as a Possible Indicator of Blast Trauma

Abstract: Forensic anthropologists have become increasingly involved in the interpretation of skeletal trauma caused by exploding ordnance. This study examines the cause and significance of butterfly fractures observed in a recent study investigating skeletal blast trauma by Christensen et al. Fractured ribs resulting from blast events carried out in the original study were re-examined revealing that rib butterfly fractures with the tensile indicator on the visceral surface were present in 100% of viable pig specimens. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 25 publications
(40 reference statements)
0
25
0
Order By: Relevance
“…). Christensen and Smith similarly observed that butterfly fracture patterning in human ribs varied based on whether the impact's three‐point bending deformation opposed or mimicked the natural curvature of the bone. Based on the high‐speed video footage in this study, three‐point bending that opposed the femur's natural curvature appears to cause a greater amount of overall deformation and rebound in these anterior (convex side) impacts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…). Christensen and Smith similarly observed that butterfly fracture patterning in human ribs varied based on whether the impact's three‐point bending deformation opposed or mimicked the natural curvature of the bone. Based on the high‐speed video footage in this study, three‐point bending that opposed the femur's natural curvature appears to cause a greater amount of overall deformation and rebound in these anterior (convex side) impacts.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study, however, indicate that inferring the impact site based on current published models may not be sufficiently accurate for use in a forensic context. The current forensic model is based on the biomechanical prediction that a bone in "three-point bending" will fracture initially on the tension side at the point of maximum strain (7,(12)(13)(14)18,19,25). The point of maximum strain is depicted in the current forensic model to be located directly opposite to the point of impact (4,12).…”
Section: Interpreting the Impact Sitementioning
confidence: 99%
“…Recent anthropological research by Christensen and Smith demonstrates the prevalence of butterfly fractures on the visceral surface of the ribs of pig specimens, positing that the blast forces are the cause of these and highlight this pattern as varying from that encountered in other types of trauma. This identifies a potential indicator of blast injury that could be used by forensic anthropologists and demonstrates that capability of identifying this type of trauma in skeletal remains.…”
Section: Applying Patterns and Indicators Of Blast Injury To Anthropomentioning
confidence: 99%
“…Primary blast injury is one of the main concerns of ongoing research, and the current medical findings have elements that would translate well to use in anthropological investigation. Current knowledge which is of use to anthropologists is summarized in Table .…”
Section: Moving Anthropology Forwardsmentioning
confidence: 99%
“…Primary blast injury is the result of blast wave overpressure and affects the air or fluid filled organs. Experimental work links primary blast injury with skeletal trauma to the ribs and traumatic amputations [8,11,12]. Secondary blast injury represents injuries caused by the fragmentation of munitions and the impact of these fragments on the human body.…”
Section: Introductionmentioning
confidence: 99%